RETRACTED: Meta-analysis of the synergistic effect of traditional Chinese medicine compounds combined with conventional Western medicine in the treatment of osteoporosis - Jin, Huan; Huang, Cai; Zhang, Yan; Dong, Ying; Xiong, Qi; Wang, Di; He, Ziyi; Shen, Lin; Ma, Chen; Wang, Zixian; Zeng, Lingfeng; Shuai, Bo (Frontiers in Endocrinology, 2025)
BackgroundAs a global public health problem, osteoporosis (OP) urgently requires better treatment strategies. This study systematically evaluated the synergistic effect of traditional Chinese medicine (TCM) compounds combined with conventional Western medicine (such as bisphosphonates and calcium) compared to Western medicine alone in the treatment of OP through a meta-analysis.MethodsBased on Preferred Reporting Items for Systematic Reviews and Meta-Analyses and the Measurement Tool for Systematic Review Assessment guidelines, databases such as PubMed and Embase were systematically searched (as of March 2025), and 13 randomized controlled trials (RCTs), involving a total of 2,403 patients, were included.ResultsThe integrated Chinese and Western medicine group showed significantly higher lumbar and femoral neck Bone mineral density (BMD) growth rates than the control group, alongside reduced pain visual analogue scale (VAS) scores. Mechanistically, the combination therapy synergistically modulated bone turnover markers: the bone resorption marker type I collagen C-terminal peptide (CTX-1) decreased (MD = -1.33, P = 0.05), the bone formation marker osteocalcin (OC) increased (MD = 15.56, P < 0.0001), suggesting dual regulation of osteoclast inhibition (e.g., via Receptor Activator of Nuclear Factor-κ B Ligand (RANKL) suppression) and osteoblast activation (e.g., via Wnt/β-catenin signaling). Notably, Procollagen I N-Terminal Propeptide (P1NP) levels remained unchanged (P = 0.63), indicating differential targeting of bone formation pathways. Subgroup analyses revealed stronger BMD improvements with short-term interventions (3–6 months), potentially linked to early osteoclast activity suppression by TCM compounds (e.g., icariin in Xianling Gubao), whereas diminished long-term efficacy (12–24 months) may reflect adaptive bone remodeling plateaus. Fracture incidence and safety profiles did not differ between groups.ConclusionCurrent evidence supports the potential of integrated TCM and Western medicine therapy in improving BMD and reducing pain. However, its clinical application requires further validation through large-scale, long-term, and standardized RCTs. Future research should focus on standardizing TCM compound ingredients, exploring the mechanisms of combined therapies, and conducting long-term safety assessmentsSystematic review registrationhttps://doi.org/10.17605/OSF.IO/G73SH.